2004
DOI: 10.1088/0031-9155/49/18/001
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of cardiovascular liver motion for the eventual application of elasticity imaging to the liverin vivo

Abstract: Elastography, which uses ultrasound to image the tissue strain that results from an applied displacement, can display tumours and heat-ablated tissue with high contrast. However, its application to liver in vivo may be problematic due to the presence of respiratory and cardiovascular sources of displacement. The aim of this study was to measure the cardiovascular-induced component of natural liver motion for the purpose of planning future work that will either use the motion to produce elasticity images or wil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 33 publications
2
22
0
Order By: Relevance
“…Additionally, the recent implementation of ARFI imaging with parallel receive tracking significantly decreases acquisition times, thus making it easier to complete data acquisition during periods of minimal physiologic motion. Kolen et al (2004) have previously evaluated cardiovascular motion in the liver for applications in elasticity imaging. Similar studies are underway to assess the limitations physiologic motion will impose on ARFI imaging, which has different acquisition protocols than elastography and generally requires individual regions of tissue to be stable for shorter periods of time.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the recent implementation of ARFI imaging with parallel receive tracking significantly decreases acquisition times, thus making it easier to complete data acquisition during periods of minimal physiologic motion. Kolen et al (2004) have previously evaluated cardiovascular motion in the liver for applications in elasticity imaging. Similar studies are underway to assess the limitations physiologic motion will impose on ARFI imaging, which has different acquisition protocols than elastography and generally requires individual regions of tissue to be stable for shorter periods of time.…”
Section: Discussionmentioning
confidence: 99%
“…These examples were selected, in part, because motion characteristics were of significantly low amplitude such that effects stemming from RF data line decorrelation would not impact analysis of motion filter performance [9]. However, the velocity and acceleration magnitudes used in this study are representative of magnitudes found in vivo [7], [9]. Additionally, the analyses provided have focused upon removing physiological motion in the lateral and axial dimension, and have ignored motion in the elevation (out-of-plane) dimension.…”
Section: Discussionmentioning
confidence: 99%
“…Motion not associated with these stimuli is generally difficult to relate to local mechanical properties and adds bias and uncertainty to elasticity measurements [7]- [9]. These secondary sources of motion often originate from unwanted transducer movements or from physiological events.…”
Section: Introductionmentioning
confidence: 99%
“…This culminates in elastograms with low signal-to-noise (SNRe) and contrast-to-noise (CNRe) ratios. Other disadvantages of external compression elastography in this application include excessive lateral and elevational motion which, when coupled with physiological motion resulting from cardiovascular and respiratory processes, further degrade elastographic image quality (Kolen et al 2002;Varghese et al 2002a;Varghese et al 2002a;Varghese et al 2002b). …”
Section: Introduction and Literaturementioning
confidence: 99%